2015
DOI: 10.7554/elife.05920
|View full text |Cite
|
Sign up to set email alerts
|

The kinase DYRK1A reciprocally regulates the differentiation of Th17 and regulatory T cells

Abstract: The balance between Th17 and T regulatory (Treg) cells critically modulates immune homeostasis, with an inadequate Treg response contributing to inflammatory disease. Using an unbiased chemical biology approach, we identified a novel role for the dual specificity tyrosine-phosphorylation-regulated kinase DYRK1A in regulating this balance. Inhibition of DYRK1A enhances Treg differentiation and impairs Th17 differentiation without affecting known pathways of Treg/Th17 differentiation. Thus, DYRK1A represents a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 85 publications
8
57
0
Order By: Relevance
“…Small molecule approaches offer the potential dual benefit of not only learning novel biology, but also the potential utility of the identified compound as a therapeutic lead. Such an approach identified DYRK1A as a novel regulator of T reg differentiation, suggesting an explanation for the hypofunctional T reg s seen in Down Syndrome ( DYRK1A is on chromosome 21) and potential clinical utility of DYRK1A inhibitors [23]. …”
Section: Clues From Human Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Small molecule approaches offer the potential dual benefit of not only learning novel biology, but also the potential utility of the identified compound as a therapeutic lead. Such an approach identified DYRK1A as a novel regulator of T reg differentiation, suggesting an explanation for the hypofunctional T reg s seen in Down Syndrome ( DYRK1A is on chromosome 21) and potential clinical utility of DYRK1A inhibitors [23]. …”
Section: Clues From Human Diseasementioning
confidence: 99%
“…Recent data suggest that rapamycin’s growth-inhibitory effects may dominantly contribute to the in vitro results and similarly impact T reg expansion in vitro and in vivo, although there may be ancillary benefits on stronger inhibition of other lineages and reducing production of pro-inflammatory cytokines [23,91,92]. Rapamycin can impair insulin signaling and may have contributed to the transient decrease in β-cell function in the IL-2/rapamycin T1D trial [87,93].…”
Section: Systemic Treg Therapiesmentioning
confidence: 99%
“…Zhao et al reported that dihydroartemisinin works by attenuating the mTOR/Akt signaling pathway (Zhao, et al, 2012). However, in a recent study, Khor et al showed that artemisinin and other 14 novel Treg cell enhancers appear to work independently of mTOR (Khor, et al, 2015). Nevertheless, accumulating evidence clearly show that most of artemisinin family drugs have potent immunosuppressive effects against T cell activation, enhance the Treg differentiation in vitro , and increase the peripheral Treg numbers in vivo .…”
Section: Artemisinin Family Drugs Exert Immune Regulatory Functionsmentioning
confidence: 99%
“…Induction of iTreg cell differentiation by CDK2 inhibition was recently confirmed with kenpaullone, another pharmacological inhibitor of CDKs [210]. Another essential kinase regulating the differentiation of Th17 and regulatory T cells is DYRK1A [211]. Inhibition of DYRK1A enhances Treg differentiation and impairs Th17 differentiation and attenuates inflammation [211].…”
Section: Roscovitine and Cystic Fibrosismentioning
confidence: 99%
“…Another essential kinase regulating the differentiation of Th17 and regulatory T cells is DYRK1A [211]. Inhibition of DYRK1A enhances Treg differentiation and impairs Th17 differentiation and attenuates inflammation [211]. As roscovitine is also a DYRK1A inhibitor (IC 50 in the μM range) [212, 34], its effect on DYRK1A may contribute to its effects on T cell differentiation.…”
Section: Roscovitine and Cystic Fibrosismentioning
confidence: 99%